Characteristics and factors associated with diameter deviation of rhexis reference circle generated by an image-guided system in cataract surgery: a cross-sectional study - Yabo Fu; Yulong Huang; Xiaobao Liu; Chishan Kang; Wenjie Wu; Qiong Li (Scientific Reports)
Abstract More attention should be paid to the deviations between the actual diameter of the rhexis reference circle which projected by the Image-guided systems and its intended size, and assess the influence of ocular biometric parameters on the deviation. In this study, the Callisto eye image-guided system was employed to generate a digital rhexis reference circle (rhexis overlay) set at an intended diameter of 6 mm and a screenshot of the video was taken at the end of the cataract surgery, then to compare the deviation between the observed rhexis overlay diameter (ROD) and the optic diameter (6 mm). The factors influencing diameter deviation were identified with univariate and multivariate linear regression. Subgroup analyses were conducted based on factors identified in the multivariate regression. And we observed that a total of 213 eyes of 174 patients were included in the final analysis. The diameter deviation averaged − 0.24 ± 0.28 mm (P = 0.0001) and was positively correlated with phakic anterior chamber depth (ACD) (P < 0.001) and negatively correlated with white-to-white (WTW) measurement (P < 0.001). Subgroup analyses revealed significantly greater diameter deviation in cases with preoperative ACD < 2.5 mm and WTW ≥ 12.0 mm (all P < 0.05). Following optimization, the mean diameter deviation was 0.00047 ± 0.26 mm (P > 0.05). In conclusion, the Callisto eye image-guided system demonstrates good precision in CCC assistance. However, there remains a slight deviation from the intended size when generating the rhexis reference circle in eyes with shallow anterior chambers and larger corneas. Implementing an optimization process could be beneficial for these eyes.